2004
DOI: 10.1210/jc.2003-032185
|View full text |Cite
|
Sign up to set email alerts
|

Altered Thyroid and Adrenal Function in Children Born at Term and Preterm, Small for Gestational Age

Abstract: Intrauterine growth retardation may permanently influence the endocrine system by affecting its programming during development. The aim of this study was to evaluate thyroid and adrenal function together with insulin sensitivity in a group of children born small for gestational age (SGA). Forty SGA children (mean age, 6.7 ؎ 1.7 yr) and 35 children born appropriate for gestational age (mean age, 6.5 ؎ 2.2 yr) were selected for the study. TSH, free T 4 , free T 3 (fT 3 ), rT 3 , antithyroid antibodies, cortisol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 38 publications
2
38
1
1
Order By: Relevance
“…Moreover, we recently reported that thyroid function is frequently altered in children born small for gestational age (SGA) (8). The aim of the present study was to confirm this finding in a larger number of children and in particular to verify the role played by prematurity per se on thyroid function later on in life.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, we recently reported that thyroid function is frequently altered in children born small for gestational age (SGA) (8). The aim of the present study was to confirm this finding in a larger number of children and in particular to verify the role played by prematurity per se on thyroid function later on in life.…”
supporting
confidence: 63%
“…In a previous study, in which we examined a group of children of the same age, we found an increased prevalence of thyroid dysfunction in those born SGA (8) and identified in the shorter length at birth the cause for the thyroid alteration. In that study, however, most of the patients were born prematurely, and there was indeed a trend toward a negative correlation between TSH levels and gestational age, which, however, did not reach statistical significance, probably because of the low number of patients examined.…”
Section: Discussionmentioning
confidence: 85%
“…Of these, 16 citations were excluded after the first screening based on the abstracts or titles, mainly because they were overlapping records, not cohort studies, or obviously irrelevant studies. After full-text review of the remaining 17 articles (8,9,10,11,12,13,14,27,28,29,30,31,32,33,34,35,36), three articles were excluded because the exposure was not relevant (32,33,36), two articles were excluded because they were not on preterm delivery (34,35), and one article was excluded because of the nested case-control design (31). Finally, 11 articles involving a total of 35 467 participants were included in our meta-analysis (8,9,10,11,12,13,14,27,28,29,30).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Various studies have shown that low birth weight is associated with higher serum DHEAS concentrations, and as a consequence predisposes to an earlier adrenarche and/or an adrenal hyperandrogenic profile in adult life (4)(5)(6)(7), though in other studies, no such association was observed (8,9). An early adrenarche appears to be associated with a higher risk of hyperandrogenism and polycystic ovaries (10,11).…”
Section: Introductionmentioning
confidence: 97%